THE ROLE OF GREEN MANUFACTURING IN ENVIRONMENTAL PERFORMANCE-ANALYTICAL STUDY AT DAR AL-WARITH PRINTING - Yasser Mahmoud Fahd; Thakaa Deyaa Al Sultane; Anwar Abd Ellah Mejbel (Scholars Digest Publishing, 2023)
The research aims primarily to determine the role of green manufacturing in improving environmental performance at the level of Dar Al-Warith Printing and Publishing Press, and based on a major problem that was diagnosed with several questions, the extent of awareness of the influential relationships between variables in the field. An expressive intellectual framework for the research was formed, as green manufacturing was adopted as a variable. It is independent and consists of four dimensions (reducing waste - recycling - reuse - redesign), and environmental performance was adopted as a dependent variable (one-dimensional), which was measured with six items. The sample consisted of (61) workers at Dar Al-Warith Printing and Publishing Press. To analyze the data, a set of statistical methods available in the statistical program (SPSS.V.25) was used. The research reached several conclusions, including (the results showed the impact relationships between manufacturing Green and the environmental performance variable. There is a high interpretation rate for the ability of green manufacturing to explain the changes that occur in environmental performance, amounting to (0.958). The research resulted in a set of recommendations, including (the printing press management should collect waste, waste, and parts resulting from industrial processes with the aim of benefiting from them in other industrial processes.
Keywords: Green Manufacturing - Environmental Performance - Dar Al-Warith Printing And Publishing Press.